1+5/6x=2+2/3x

Simple and best practice solution for 1+5/6x=2+2/3x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 1+5/6x=2+2/3x equation:



1+5/6x=2+2/3x
We move all terms to the left:
1+5/6x-(2+2/3x)=0
Domain of the equation: 6x!=0
x!=0/6
x!=0
x∈R
Domain of the equation: 3x)!=0
x!=0/1
x!=0
x∈R
We add all the numbers together, and all the variables
5/6x-(2/3x+2)+1=0
We get rid of parentheses
5/6x-2/3x-2+1=0
We calculate fractions
15x/18x^2+(-12x)/18x^2-2+1=0
We add all the numbers together, and all the variables
15x/18x^2+(-12x)/18x^2-1=0
We multiply all the terms by the denominator
15x+(-12x)-1*18x^2=0
Wy multiply elements
-18x^2+15x+(-12x)=0
We get rid of parentheses
-18x^2+15x-12x=0
We add all the numbers together, and all the variables
-18x^2+3x=0
a = -18; b = 3; c = 0;
Δ = b2-4ac
Δ = 32-4·(-18)·0
Δ = 9
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:
$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}$
$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}$

$\sqrt{\Delta}=\sqrt{9}=3$
$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(3)-3}{2*-18}=\frac{-6}{-36} =1/6 $
$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(3)+3}{2*-18}=\frac{0}{-36} =0 $

See similar equations:

| 1/(y-1)+1/(y+1)=1 | | 4(w-4)-6w=-28 | | 9(w^2+1=9 | | -8=4.3+c | | 3x+6=102 | | f/(f/2)-4=1 | | 3r+15=5r-25 | | 2x-8=1x+1 | | (3x-1)^.3333=4 | | 2.1/2p=-4.7 | | 1x-5=2x+2 | | y-7/8y=9 | | 2x-30+5x=12 | | -r+34=3(r+6) | | 1x+13=5x+1 | | (3x-1)^1/3=4 | | 5y-21=3(y-5) | | 4x-20-4x-2=-2 | | n+1.7=14 | | -72x-83=-83-72x | | 8k-28+3k-9=46 | | 1+1+y=3 | | 2x-3=-(4x-15 | | 31.2=5.2a | | 3^4=w+2^5 | | 2x-6=3x-23 | | -8+10x=10 | | 2c-8=4 | | 8x+20=52x | | 125m-100m+42,750=45,900-200m | | (-3)(x/12)=1 | | 7+2n=7-2n |

Equations solver categories